What Makes Hiring Difficult? Evidence from Linked Survey-Administrative Data - Antoine Bertheau; Birthe Larsen; Zeyu Zhao (Institute of Labor Economics (IZA), 2023)
We design a survey that asks firms about the obstacles that discourage them from hiring despite having potential needs. Using Danish administrative data and subjective beliefs elicited from our survey, we show how hiring obstacles vary across firms. Over two-thirds of employers agree that skill shortages are a hiring obstacle. One-third of employers consider labor costs, the time to find candidates, and the time to train new recruits as hiring obstacles. High-wage firms are less discouraged by labor costs, while younger or smaller firms are more discouraged by search and training time. Around thirty percent of employers prefer to hire the already employed over the unemployed because they believe that unemployed workers have lower abilities due to negative selection or skill depreciation during unemployment. Firms with such preferences are more likely to report hiring obstacles.
Keywords: J23; M12; 330; labor demand; hiring behavior; linked survey-administrative data; employer perceptions